Peran Penyuluh Agama dalam Memperkuat Kerukunan Umat Beragama di Distrik Teluk Patipi Kabupaten FakFak - Lulu Aufa Hibrizi; Widayat Mintarsih; Ema Hidayanti (Institut Agama Islam Negeri Fattahul Muluk Papua, 2026)
Religious counsellors play an important role in fostering religious life and maintaining religious harmony, particularly in Teluk Patipi District, FakFak Regency, West Papua Province. This study aims to analyse the role, strategies, and obstacles faced by religious counsellors in strengthening religious moderation and social cohesion. This is a qualitative study using a case study approach, through data collection from interviews, field observations, and documentation studies. The results show that religious counsellors function not only as conveyors of religious teachings, but also as agents of social transformation who act as cultural mediators, moral educators, community facilitators, and agents of peace when problems arise between religious communities. The role of counsellors is very important in strengthening religious harmony. The strategies applied include communicative, educational, socio-practical, and adaptive approaches based on local wisdom, such as the philosophy of ‘One Stove, Three Stones’. However, there are various structural, competency, and socio-ideological obstacles, including limited resources, digital literacy challenges, and resistance to religious moderation that religious counselors must face. This study concludes that the success of religious counsellors in multicultural societies depends on their ability to adapt to the local context, build effective communication, and apply inclusive counselling methods. Thus, religious counsellors play an important role in strengthening religious harmony, maintaining social cohesion, and building a faithful, characterful, and harmonious society amid the dynamics of modernisation and globalisation.